Antigenic heterogeneity of the non-serogroup antigen structure of Neisseria gonorrhoeae lipopolysaccharides. - Apicella, M A (1979)
Studies of the antigenic structure of the polysaccharide component of gonococcal lipopolysaccaride (LPS) indicated that the non-serogroup antigen structure is antigenically heterogeneous. Immunodiffusion studies of Gc4 strain 8551 indicated that in addition to the Gc serogroup determinent, this polysaccharide contains two other sets of determinants, one which is shared with the other five Gc serogroups and a second which is shared by the Gc1 and Gc3 serogroups. Enzyme-linked immunosorbent assay (ELISA) studies confirmed the immunodiffusion, documented qualitative differences, and suggested that quantitative differences may exist in the common determinant from serogroup to serogroup. As measured by ELISA inhibition, native LPS showed the same antigenic arrangement as the purified LPS polysaccharides. Studies with LPS-derived polysaccharides from nonprototype strains in immunodiffusion gave results identical to the prototype strains. This antigen variation, although distinct from serogroup specificity, was related to the serogroup determinant.